The Principle of Proportionality in Drug Control Policy in the Philippines and Indonesia - Asmak ul Hosnah; Weldy Jevis; Jufel D. Fernandez (Sriwijaya Law Review, 2025)
The war on drugs has become a global concern, particularly in Southeast Asia, where drug-related crimes are considered a serious threat to national and international security. Two cases that will be discussed relate to the anti-drug campaigns in the Philippines and Indonesia, both of which have attracted attention due to their controversial law enforcement methods. This study aims to compare the application of the principle of proportionality in drug law enforcement in both countries, focusing on whether the actions taken align with international human rights standards. This research employs a juridical-comparative method, analysing legal policies, government policies, and human rights-related case facts from both countries. In the Philippines, the campaign under President Duterte's administration raised significant concerns regarding extrajudicial killings and the excessive use of power, which deviates from the principle of proportional enforcement. In contrast, Indonesia adopts a more judicial approach, although it still faces criticism for harsh verdicts and the implementation of the death penalty. The findings will reveal significant differences in how the principle of proportionality is interpreted and applied, influenced by political will, law, and institutional accountability. While both countries claim to uphold the rule of law, the level of adherence to the principle of proportionality varies greatly. This study concludes that a balanced and human rights-based approach is essential for sustainable and ethical enforcement of drug policy in Southeast Asia.